CALCULATED RISKS: EXPLORING PLAGUE ETHICS WITH LUTHER AND BARTH - A. Hancock (Acta Theologica)
This article explores the way churches in the USA navigated risk in the early months of the COVID-19 pandemic. In particular, it examines the theological basis for reactions to restrictions affecting in-person worship services and for participation in the Black Lives Matter protests. The article argues that the ongoing conversation about health and risk in the American church would benefit from additional theological perspectives. Martin Luther’s 1527 treatise on plague ethics and Karl Barth’s treatment of the “will to health” in Church Dogmatics are discussed with attention to questions of health and risk. With these texts from Luther and Barth in view, the article returns to questions of risk, worship, and protest in the context of the pandemic, outlining six potential fruitful themes for ongoing conversation and discernment.